2014
DOI: 10.1108/md-05-2013-0279
|View full text |Cite
|
Sign up to set email alerts
|

Organizational design and pricing capabilities for superior firm performance

Abstract: Purpose – The purpose of this paper is to test the relationship between organizational antecedents, pricing capabilities, and firm performance. Design/methodology/approach – Quantitative survey of 748 managers from mostly large companies globally. Findings – It was found that the following five key organizational resources (the 5 Cs) – center-led price management, organizational c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 78 publications
0
37
0
Order By: Relevance
“…Thus, this pricing orientation motivates firms to implement better expenditures modules. Again, Liozu et al (2014) explain in a comparative study on SMEs found that more companies base their pricing on cost and implement cost models which use contributions and profits margin objectives to determine their pricing. Based on the analysis of the significance of cost-oriented pricing, the following study hypothesized that:…”
Section: Cost-oriented Pricingmentioning
confidence: 99%
“…Thus, this pricing orientation motivates firms to implement better expenditures modules. Again, Liozu et al (2014) explain in a comparative study on SMEs found that more companies base their pricing on cost and implement cost models which use contributions and profits margin objectives to determine their pricing. Based on the analysis of the significance of cost-oriented pricing, the following study hypothesized that:…”
Section: Cost-oriented Pricingmentioning
confidence: 99%
“…Finally, the total economic value can be determined and communicated by adding the price of the next best alternative and the benefits of the differentiation. To manage these tasks, providers must improve their pricing capabilities and resources when implementing a value-based pricing approach (Dutta et al, 2003;Liozu et al, 2014), overcome a set of challenges (Hinterhuber, 2008;Gale and Swire, 2012) and adjust the organizational design (Liozu et al, 2014). Some concepts consider approaches that contribute to customers' value throughout the entire life cycle (for example, total cost or total profit of ownership) to quantify and communicate the value of an offer (Ulaga and Chacour, 2001;Snelgrove, 2012).…”
Section: Selling Schemementioning
confidence: 99%
“…& Lyytinen, 2006;Kohlbacher & Reijers, 2013;Liozu, Hinterhuber& Somers, 2014). Similarly, it is assumed in this article that the organizational effects are related to the internal consistency of the mentioned organizations elements, and that the greater alignment of the elements is related to the better organizational performance.…”
mentioning
confidence: 95%